Shoshannat Yaaqov : Jewish and Iranian studies in honor of Yaakov Elman - Elman, Yaakov; Secunda, Shai.; Fine, Steven (Leiden ; Boston : Brill, 2012)
Shoshannat Yaakov includes studies by leading scholars on Ancient Jewish and Iranian Studies and essays that combine both fields in the new discipline of Irano-Talmudica.
Includes bibliographical references.
Print version record.
Articles in English and some in Hebrew.
Master record variable field(s) change: 050, 082
Keywords: Talmud -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Judaism -- Influence; Iran -- Civilization -- Jewish influences -- To 640.; Iran -- Intellectual life -- To 640.; Sassanids -- Intellectual life; RELIGION -- Judaism -- General; Electronic books